2021
DOI: 10.1038/s41598-021-92086-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene reduces glucose sensitivity and reverses photosynthetic repression through optimization of glutathione production in salt-stressed wheat (Triticum aestivum L.)

Abstract: Ethylene plays a crucial role throughout the life cycle of plants under optimal and stressful environments. The present study reports the involvement of exogenously sourced ethylene (as ethephon; 2-chloroethyl phosphonic acid) in the protection of the photosynthetic activity from glucose (Glu) sensitivity through its influence on the antioxidant system for adaptation of wheat (Triticum aestivum L.) plants under salt stress. Ten-day-old plants were subjected to control and 100 mM NaCl and treated with 200 µl L−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 76 publications
3
38
0
Order By: Relevance
“…Notably, maximum ethylene generation was achieved in heat-stressed plants; this was stress ethylene, and adversely affected plant growth. Several prior studies have described stress-induced ethylene formation and the importance of optimal ethylene levels [43,46]. The observed stress ethylene was reduced by ethephon application, which brought ethylene levels to an optimum and influenced the physiological and metabolic changes associated with high-temperature stress.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Notably, maximum ethylene generation was achieved in heat-stressed plants; this was stress ethylene, and adversely affected plant growth. Several prior studies have described stress-induced ethylene formation and the importance of optimal ethylene levels [43,46]. The observed stress ethylene was reduced by ethephon application, which brought ethylene levels to an optimum and influenced the physiological and metabolic changes associated with high-temperature stress.…”
Section: Discussionmentioning
confidence: 95%
“…Through transcriptomic analysis studies, Smet and colleagues [94] determined that the expression of photosynthetic genes was altered in ethylene-treated Arabidopsis plants exposed to high CO 2 concentrations. Salt stress in wheat plants was found to suppress genes encoding PSII proteins; however, pretreatment with ethylene caused those same genes to beup-regulated instead [46]. Here, the effect of ethylene on genes encoding core PSII proteins in rice plants subjected to high-temperature stress was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethylene signaling has been found to increase the accumulation of proline for osmotic adjustment [ 22 ]. It was reported that enhanced activity of ascorbate–glutathione cycle enzymes produced higher concentrations of GSH that reduced salt and excess glucose-induced oxidative stress in Triticum aestivum [ 23 ]. Salt tolerance was associated with increased relative water content, lower lipid peroxidation, and increased proline and polyamine accumulation accompanied by increased ethylene [ 24 ].…”
Section: Introductionmentioning
confidence: 99%